Facial color processing in the face‐selective regions: An fMRI study. Issue 9 (23rd April 2014) - Nakajima, Kae; Minami, Tetsuto; Tanabe, Hiroki C.; Sadato, Norihiro; Nakauchi, Shigeki
Abstract Facial color is important information for social communication as it provides important clues to recognize a person's emotion and health condition. Our previous EEG study suggested that N170 at the left occipito‐temporal site is related to facial color processing (Nakajima et al., [2012]: Neuropsychologia 50:2499–2505). However, because of the low spatial resolution of EEG experiment, the brain region is involved in facial color processing remains controversial. In the present study, we examined the neural substrates of facial color processing using functional magnetic resonance imaging (fMRI). We measured brain activity from 25 subjects during the presentation of natural‐ and bluish‐colored face and their scrambled images. The bilateral fusiform face (FFA) area and occipital face area (OFA) were localized by the contrast of natural‐colored faces versus natural‐colored scrambled images. Moreover, region of interest (ROI) analysis showed that the left FFA was sensitive to facial color, whereas the right FFA and the right and left OFA were insensitive to facial color. In combination with our previous EEG results, these data suggest that the left FFA may play an important role in facial color processing. Hum Brain Mapp 35:4958–4964, 2014. © 2014 Wiley Periodicals, Inc.